Fouling on laser-fabricated model surface reliefs of functional food-industry materials. (1st December 2022) - Nastulyavichus, A A; Smirnov, N A; Khaertdinova, L F; Tolordava, E R; Yushina, Yu K; Rudenko, A A; Ionin, A A; Kudryashov, S I; Gonchukov, S A
Abstract: A typical food industry material (stainless steel) was laser-textured to evaluate biofouling of model surface relief. Both initial and laser-textured surfaces were characterized by scanning electron microscopy, energy-dispersive x-ray radiation, Raman spectroscopy, and scanning probe microscopy to reveal the most important pre-requisites for their biofouling by food pathogen bacteria.